The evolution of mechanisms involved in vertebrate endothermy - Legendre, L; Davesne, D (Royal Society, 2023)
Endothermy, i.e. the endogenous production of metabolic heat, has evolved multiple times among vertebrates, and several strategies of heat production have been studied extensively by physiologists over the course of the 20th century. The independent acquisition of endothermy by mammals and birds has been the subject of many hypotheses regarding their origin and associated evolutionary constraints. Many groups of vertebrates, however, are thought to possess other mechanisms of heat production, and alternate ways to regulate thermogenesis that are not always considered in the palaeontological literature. Here we perform a review of the mechanisms involved in heat production, with a focus on cellular and molecular mechanisms, in a phylogenetic context encompassing the entire vertebrate diversity. We show that endothermy in mammals and birds is not as well defined as commonly assumed by evolutionary biologists, and consists of a vast array of physiological strategies, many of which currently unknown. We also describe strategies found in other vertebrates, which may not always be considered endothermy, but nonetheless correspond to a process of active thermogenesis. We conclude that endothermy is a highly plastic character in vertebrates, and provide a guideline on terminology and occurrences of the different types of heat production in vertebrate evolution.